Crisis interventions in online psychological counseling - Silva,Juliana Amaral Medeiros da (2015)
Introduction: The world's population is often assailed by crises of various orders. Disasters caused by nature and by humans themselves also impact on people's mental health. Psychological crises, such as suicide attempts, represent a growing problem in mental health. When faced with such scenarios, specific strategies of crisis intervention are both appropriate and necessary. Objective: To conduct a systematic review of the literature dealing with online psychological crisis intervention, describing and discussing their operational design, specific characteristics and applications. Method: A systematic review of literature indexed on the PubMed, PsycINFO, and SciELO databases identified by searches conducted from January to June of 2014. Results: The searches identified 17 empirical studies about online crisis interventions which were reviewed. Three crisis contexts emerged: 1) disasters, 2) risk/prevention of suicide, and 3) trauma. Eleven different intervention programs were described and the predominant treatment approach was cognitive behavioral therapy. The results showed that research into online psychological crisis intervention has been conducted in several different countries, especially the Netherlands and Australia, and that the users of these tools benefit from them. Conclusion: Online crisis interventions have been developed and researched in many countries around the world. In Brazil, there is still a lack of investment and research in this area.